A Case‐Based Reasoning (CBR) Model for the Integration of Insurance Policy and Regulations in Professional Physical Therapist Education. Issue 2 (2015) - Cohn, Rhea; Harwood, Kenneth J.; Richards, Heather; Schlumpf, Karen
Abstract : Background and Purpose. : The evolving health care environment brought about by health care reform and constantly changing insurance and regulatory requirements poses a great challenge for today's physical therapists (PTs). Because professional level PT students are expected to integrate these requirements into patient management, educational programs should explore ways to enhance student learning in these areas. The purpose of this manuscript was to describe a case‐based reasoning (CBR) approach to integrating insurance, regulations, and documentation content into a professional level PT education program, assess the outcome on students' clinical performance, and report faculty perceptions of the curricular changes. Method/Model Description and Evaluation. : Faculty in a professional level PT education program developed a CBR instructional method to integrate insurance, regulatory, and documentation content throughout the curriculum. The goals for the curriculum change were to have thirdyear students begin their internships with the ability to analyze and apply appropriate insurance and regulatory policies to all patient cases, appreciate how policies affect patient management and access, and effectively document in the medical record. In addition to adding didactic material and interactive learning experiences, faculty modified existing cases used in clinical management courses. This modification resulted in students experiencing progressively more complex clinical cases layered with insurance and regulatory challenges. Outcomes. : To determine the effectiveness of the CBR method, student performance was measured using 2 domains (financial management, documentation) of the Clinical Performance Instrument (CPI) during the student terminal clinical internship for 2 cohorts of students. The first cohort included all PT students for the 2 years prior to the implementation of CBR experiences, while the second cohort included 2 years of PT students who participated in CBR learning. Significant statistical differences between cohorts were demonstrated in student self‐assessment of documentation performance at midterm ( P = .011) and financial resources performance at the midterm and final rating periods ( P = .022 and P = .012, respectively). For clinical instructor (CI) ratings, there was a statistically significantly difference between cohorts at the final rating for financial resources performance ( P = .044), indicating a higher CI rating for those students that participated in the CBR instruction. Participating faculty survey results demonstrated that the CBR approach benefitted student learning, was not difficult to integrate into existing course learning experiences, and enhanced faculty learning. However, participating faculty had concerns regarding their own comfort level with the material and whether it was replacing more clinically oriented content. Discussion and Conclusion. : The outcomes generally support the effectiveness of the CBR approach for integrating insurance policy, regulations, and documentation in a professional level PT education program. Students learn to use regulation and insurance policy information when making clinical decisions and participating faculty did not feel unduly burdened by the integration of this content into established case studies. Although the results are encouraging, further research is recommended.